Studi komparasi strategi pembelajaran drta dan pqrst terhadap keterampilan membaca pemahaman ditinjau dari minat membaca - Dyah Putri Prastitiningtyas; St. Y. Slamet; Joko Daryanto (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
This research aims to (1)  know the differences in reading comprehension skills between students taught using the Directed Reading Thinking Activity (DRTA) learning strategy and the Preview Question Read Summarize Test (PQRST) learning strategy; (2) know the differences in reading comprehension skills between the student who has high reading interest and low reading interest; (3) know the interaction between learning strategies and reading interest on students' reading comprehension skills. The study population was all grade IV students of Laweyan District Elementary School, Surakarta 2019/2020 Academic Year. Samples were taken by cluster random sampling technique. Samples obtained from this technique are SD Negeri Pajang 1 No.93 and SD Karangasem No.61 as the experimental class while SD Bratan III and SD Pajang IV as the control class. The results showed that first, there are differences in the reading comprehension skills of students taught using the Directed Reading Thinking Activity learning strategy and students who were taught using the Preview Question Read Summarize Test; second, there are differences in reading comprehension skills between the student who has high reading interest and students who have low reading interest; third, there is no interaction between learning strategies and reading interest in reading comprehension skills.